2020
DOI: 10.1080/23802359.2020.1750983
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the hydrothermal vent provannid snail Alviniconcha boucheti (Gastropoda: Abyssochrysoidea) from the North Fiji Basin

Abstract: The family Provannidae is endemic to chemosynthetic environments in the deep-sea. Here, we report the complete mitogenome of a provannid vent snail Alviniconcha boucheti from the North Fiji Basin for the first time. The length of mitogenome was 15,981 bp, with 67.7% AT content. The mitogenome content and its protein-coding gene organization resembled those of other provannid snails. According to the phylogenetic tree, A. boucheti was most closely related to Ifremeria nautilei. Along with this result, further m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The phylogeny of Stromboidea, a superfamily in Littorinimorpha, was studied based on 13 mitochondrial protein-coding genes [18]. A phylogenetic study based on the mt genomes of deep-sea gastropods from Abyssochrysoidea indicated that this superfamily belonged to Littorinimorpha [19,20], but up to now, in the MolluscaBase (www.molluscabase.org), (accessed on 5 September 2023) their taxonomic status of order level remains uncertain [21].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogeny of Stromboidea, a superfamily in Littorinimorpha, was studied based on 13 mitochondrial protein-coding genes [18]. A phylogenetic study based on the mt genomes of deep-sea gastropods from Abyssochrysoidea indicated that this superfamily belonged to Littorinimorpha [19,20], but up to now, in the MolluscaBase (www.molluscabase.org), (accessed on 5 September 2023) their taxonomic status of order level remains uncertain [21].…”
Section: Introductionmentioning
confidence: 99%